From branding to behavior: investigating the impact of employer branding and organizational reputation on application intentions through person-organizational fit (POF) - Hadi, Faizal Susilo (Faculty of Business and Economics, University of Surabaya, 2026)
This study examines the effects of employer branding and perceived employer reputation on intention to apply for a job among Generation Z, with person-organization fit acting as a mediating variable. Using a quantitative research design, data were collected through a survey of 320 final-year university students and recent graduates in Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both employer branding and employer reputation have a significant positive influence on person-organization fit. Employer branding also demonstrates a direct and significant effect on intention to apply. In contrast, employer reputation does not directly influence intention to apply but exerts an indirect effect through person-organization fit, which itself significantly predicts intention to apply. These results highlight that Generation Z places strong emphasis on value congruence between themselves and prospective employers when making job application decisions. The study contributes to the theoretical development of job-seeking behavior by clarifying the mediating role of person-organization fit and offers practical insights for organizations in designing authentic employer branding and reputation management strategies aligned with the values of Generation Z to enhance their attractiveness in the labor market.